A Comparative Study between the Use of Problem Based Learning Method and Expository Learning Method in SPLDV Material on Students' Mathematical Concept Understanding - Sitio, Hetdy; Sinaga, D. Yuliana (Universitas Pahlawan Tuanku Tambusai, 2022)
Differences in Students' Mathematical Concept Understanding Ability Using Problem Based Learning (PBL) Learning Methods With Expository Learning Methods. On the Material System of Linear Equations of Two Variables in Class VIII SMP Negeri 8 Pematangsiantar. This study aims to determine the difference in the ability to understand mathematical concepts of students using the Problem Based Learning (PBL) learning method with the expository learning method on the material of a two-variable linear equation system. The population in this study were all eighth grade students of SMP Negeri 8 Pematangsiantar . sampling , the experimental class research sample was obtained as many as 32 students. The instrument used was a learning outcome test in the form of description questions that had been carried out at SMP Negeri 8 Pematangsiantar. From the results of the study, the average pretest result = 30.29 and the average posttest result = 34.9. Then the homogeneity of the data was tested by using the homogeneity test of variance F hit = 1.77 < F (0.05; 29:30 = 1.89 with a confidence level of = 0.05 meaning the sample is homogeneous because F hit is not in the critical area. From the calculation results of the t hit price = 1.86 for = 0.05 and v = 59 and table = 1.67 it turns out that t hits are in the k-point area, because 1.86> 1.67. So it can be concluded that student learning outcomes are good Using Problem Based Learning Methods With Expository Methods on Materials Two Variable Linear Equation System (SPLDV) in Class VIII SMP Negeri 8 Pematangsiantar.